Implementasi Festival Ramadhan Ceria sebagai Media Edukasi Nilai Keislaman dan Pengenalan Keuangan Syariah pada Siswa Sekolah Dasar di SDN 1505 Pasir Julu - Muhammad Amsal Nasution; Aminah Lubis; Nur Jannah Nasution; Zaharo Arjuna; Juliani Hasibuan; Syahrial Rizki Hsb (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Community Service is one of the implementations of the Tri Dharma of Higher Education, aiming to apply students’ academic knowledge directly within society. This activity was carried out by fifth-semester students of the Islamic Banking Study Program through the organization of the Festival Ramadhan Ceria at SDN 1505 Pasir Julu. The program aimed to instill Islamic values, enhance basic understanding of Islamic finance, and foster religious and social character among elementary school students during the month of Ramadan. The implementation method employed an educational and participatory approach through various activities, including Islamic competitions, educational games, simple counseling on saving based on Islamic principles, and socio-religious activities. The results of the program indicated increased enthusiasm and active participation among students, improved understanding of Ramadan values, and early awareness of Islamic financial concepts. In addition to benefiting the students, this community service activity also served as a practical learning experience for university students in developing soft skills, leadership, teamwork, and social awareness. Therefore, the Festival Ramadhan Ceria proved to be an effective medium for strengthening the relationship between higher education institutions and the community, while also contributing positively to the character development of elementary school students.